Determination of potential fisheries areas based on trophic status (Case study in Situ Gede, Tasikmalaya) - Sevi Sawestri; Ni Komang Suryati; Dina Muthmainnah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
Situ Gede is one of the artificial lakes/reservoirs in Tasikmalaya, West Java. The lake has functioned as a source of household water needs, fisheries, and tourism. According to determine the development of water management requires information on the trophic status and water quality. This study aimed to obtain information on the trophic status and water quality of Situ Gede. The research was conducted in Situ Gede, Tasikmalaya, West Java, in 2018. Measurement and analysis of water quality parameters used the SNI and APHA methods, while the measurement of trophic status used the Carlson Trophic State Index (TSI). The relationship between water quality parameters and TSI scores was analyzed using Statistica version 8. Based on the analysis, the trophic status of Situ Gede ranged from 69.06-79.04, with an average of 74.61. This value indicated that Situ Gede's trophic status was on a eutrophic level. The physical and chemical parameters that affect the trophic status of Situ Gede are TP, pH, conductivity, TDS, and temperature. The TP values, conductivity, pH, and temperature at Situ Gede were still categorized as normal. The trophic of Situ Gede can be a source of fish growth. Moreover, in general, Situ Gede waters still have sufficient water quality for fish life. Therefore, Situ Gede has the potential to capture fisheries, recreational fisheries, and aquaculture.Keywords:Trophic statusSitu GedeFisheryChlorophyll-aFish Reserve